ANALISIS KEBUTUHAN IMPLEMENTASI PROJECT BASED LEARNING BERBASIS STEM UNTUK MENGEMBANGKAN LITERASI NEUROSAINS PADA MATERI SISTEM SARAF - Ummiyah, Auliyau; Aminuddin Prahatama Putera; Atiek Winarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The nervous system is one of the biology topics that is complex and abstract, often causing difficulties for students in understanding its concepts and mechanisms. Learning activities that remain focused on memorization have not optimally developed students' neuroscience literacy. In fact, neuroscience literacy is essential in helping students understand the functions of the nervous system and their applications in everyday life. This study aimed to analyze the need for implementing a STEM-based Project Based Learning (PjBL) model in nervous system learning to develop students' neuroscience literacy. The study employed a descriptive method using questionnaires, semi-structured interviews, and documentation involving biology teachers and students. The findings revealed that nervous system learning is still dominated by teacher-centered conventional methods, cognitive assessment is limited to levels C1–C3, and students experience difficulties in understanding abstract concepts and relating learning materials to real-life contexts. Furthermore, teachers have not yet possessed adequate learning tools to support the implementation of STEM-based PjBL in developing neuroscience literacy. Therefore, the development of a STEM-based PjBL learning model is needed to facilitate students in improving conceptual understanding, scientific reasoning, and contextual application skills related to nervous system topics.